EXPLORING THE ROLE OF TAX PLANNING IN ENHANCING CORPORATE FINANCIAL PERFORMANCE AND COMPLIANCE - Suganda, Uce Karna; Buchory, Herry Achmad; Riana, Nia (KRIEZ ACADEMY : Journal of development and community service, 2024)
Background:Tax planning is an integral component of corporate financial management, and its role in improving financial performance while ensuring compliance with tax regulations has become a focal point in both academic and practical financial studies. With evolving tax laws, global business dynamics, and increasing scrutiny on corporate tax practices, efficient tax planning is crucial for companies to maintain financial stability and ensure compliance. This research explores how tax planning strategies can enhance a corporation’s financial performance while adhering to regulatory frameworks, providing insight into the symbiotic relationship between tax optimization and corporate governance. Aims:The aim of this research is to investigate the role of tax planning in enhancing corporate financial performance and ensuring compliance with tax laws. It seeks to highlight the importance of effective tax planning strategies in improving profitability, optimizing cash flow, and minimizing tax liabilities while maintaining transparency and adhering to tax regulations. Research Method:This study adopts a mixed-methods approach, combining both qualitative and quantitative techniques. It includes case studies of multinational corporations and surveys of finance professionals to assess the relationship between tax planning strategies, financial performance, and compliance levels. Data is analyzed using statistical methods to examine correlations between tax planning practices and key financial metrics. Results and Conclusion:The results indicate that effective tax planning significantly contributes to improved financial performance, including enhanced profitability and liquidity. However, the research also highlights challenges related to regulatory compliance, with some companies facing issues of transparency and tax avoidance. The conclusion stresses the importance of balancing tax efficiency with ethical practices and legal compliance to achieve sustainable financial growth. Contribution:This research contributes to the understanding of the intricate relationship between tax planning and corporate financial performance. It provides practical insights for businesses and policymakers on how to enhance financial outcomes while navigating the complexities of tax regulations.